The Politics of Chaos in the Middle East: By Olivier Roy (New York: Columbia University Press, 2008. 165 pages.) (American Journal of Islam and Society, 2009)
This relatively short and succinct book, written by a prominent French politicalanalyst, offers an insight not only into post-9/11 American military andstrategic dilemmas, but also a glimpse into the respective European conceptionsand ways of thinking. Its main thrust is that the American reaction tothe events of that day, far from producing an outcome in the image of a“hyperpower in a unipolar world,” has instead bogged it down as a “powertied up in knots, incapable of policing the world” (p. 3). This “hopeless” situation,according to Roy, was brought on the Americans by themselves,rather than as a result of their enemies, be they the Taliban, al-Qaeda, or Iran(p. 3). While the American invasion of Iraq produced deep geostrategictransformations in the Middle East, these did not always produce the resultsthat American decision makers had countenanced ...